Factors Influencing Audience’s Urban Preference through Mobile-Enabled Music - Zhu, Zhi-Hui; Chen, Han-Ying (International Review of Management and Marketing, 2024)
People’s perception of and preference for cities have a close relationship with the shaping and transmission of the city’s image. This article explores the factors that influence the audience’s city preference by applying empathy theory to the mobile urban music “Xi'an People’s Song.” The branding of urban music and its mobile socialization appear to affect urban music empathy positively, although awareness has no significant effect. Urban music empathy fully mediates between branding and goodwill and between the social function of urban music and goodwill. However, the moderating effect of people’s familiarity with urban culture is not significant for urban music empathy and urban preference. The hypothesized relationships are further illustrated on this basis, and the optimization of urban music as a creative medium for promoting city image is discussed.